The abnormal level of HSP70 is related to Treg/Th17 imbalance in PCOS patients - Yiqing Yang (BMC, 2021)
Abstract Background Polycystic ovary syndrome (PCOS) is a disease with chronic nonspecific low-grade inflammation. The imbalance of immune cells exists in PCOS. Several studies have found that heat shock protein 70 (HSP70) may be involved in the immunological pathogenesis of PCOS, but the relationship between HSP70 and Regulatory T cell (Treg)/T helper cell 17(Th17) ratio remains unclear. This study aims to explore the correlation between HSP70 and Treg/Th17 ratio and to provide evidence for the role of HSP70 in the immunological etiology of PCOS. Results There was no significant difference in age and body mass index (BMI) between the two groups. The concentrations of basal estradiol (E2), basal follicle-stimulating hormone (FSH) did not show a significant difference between the two groups. The concentrations of basal luteinizing hormone (LH) (P < 0.01), testosterone (T) (P < 0.01), glucose (P < 0.001) and insulin (P < 0.001) in PCOS patients were significantly higher than those in the control group. The protein levels of HSP70 were significantly higher in serum in the PCOS group (P < 0.001). The percentage of Treg cells was significantly lower (P < 0.01), while the percentage of the Th17 cells of the PCOS group was significantly higher than that of the control group (P < 0.05). The ratio of Treg/Th17 in the PCOS group was significantly lower (P < 0.001). The concentrations of Interleukin (IL)-6, IL-17, and IL-23 were significantly higher, while the levels of IL-10 and Transforming growth factor-β (TGF-β) were significantly lower in the PCOS group (P < 0.001). Spearman rank correlation analysis showed a strong negative correlation of serum HSP70 levels with Treg/Th17 ratio, IL-10, and TGF-β levels. In contrast, HSP70 levels were significantly positively correlated with IL-6, IL-17, IL-23, LH, insulin, and glucose levels. Conclusion The abnormal level of HSP70 is correlated with Treg/Th17 imbalance and corresponding cytokines, which indicates that HSP70 may play an important role in PCOS immunologic pathogenesis.